Involvement of a Non-Human Sialic Acid in Human Cancer - Samraj, Annie; Läubli, Heinz; Varki, Nissi; Varki, Ajit (Frontiers in Oncology, 2014)
Sialic acids are common monosaccharides that are widely expressed as outer terminal units on all vertebrate cell surfaces, and play fundamental roles in cell-cell and cell-microenvironment interactions. The predominant sialic acids on most mammalian cells are N-glycolylneuraminic acid (Neu5Gc) and N-acetylneuraminic acid (Neu5Ac). Neu5Gc is notable for its deficiency in humans, due to a species-specific and species-universal inactivating deletion in the CMAH gene encoding the hydroxylase that converts CMP-Neu5Ac to CMP-Neu5Gc. However, Neu5Gc is metabolically incorporated into human tissues from dietary sources (particularly red meat), and detected at even higher levels in some human cancers. Early life exposure to Neu5Gc containing foods in the presence of certain commensal bacteria that incorporate dietary Neu5Gc into lipooligosaccharides can lead to generation of antibodies that are also cross-reactive against Neu5Gc-containing glycans in human tissues (“xeno-autoantigens”). Such anti-Neu5Gc “xeno-autoantibodies” are found in all humans, although ranging widely in levels among individuals, and displaying diverse and variable specificities for the underlying glycan. Experimental evidence in a human-like Neu5Gc deficient Cmah-/- mouse model shows that inflammation due to “xenosialitis” caused by this antigen-antibody interaction can promote tumor progression, suggesting a likely mechanism for the well-known epidemiological link between red meat consumption and carcinoma risk. In this review, we discuss the history of this field, mechanisms of Neu5Gc incorporation into tissues, the origin and specificities of human anti-Neu5Gc antibodies, their use as possible cancer biomarkers, implications of xenosialitis in cancer initiation and progression, and current and future approaches towards immunotherapy that could take advantage of this unusual human-specific phenomenon.